you should use brackets so it looks like
you are on the right track, after multiplying top and bottom by sinx - cosx you get
LS = (1+tanx)(sinx-cosx)/(sin^2 x - cos^2 x)
= (sinx - cosx + sin^2 x/cosx - sinx)/(sin^2x - cos^2x) after expanding
= (sin^2x - cos^2)/cosx ÷ (sin^2x - cos^2x)
#30 seems to work the same way.
i dont understand the second step..did u turn tan into sin/cos..? because im trying to do it and i cant get it
wat i did for the top is
and then sinx-cosx+sin^2/cosx-cosx
can the two cos at the end cancel..thats wats screwing me up i think
here is my multiplication for the top
(1+ sinx/cosx)(sinx-cosx) or
sinx - cosx + sin^2x/cosx - sinx/cosx * cosx
= sinx - cosx + sin^2x/cosx - sinx
= -cosx + sin^2x/cosx , now take a common denominator
= (-cos^2x + sin^2x)/cosx
= (sin^2x - cos^2x)/cosx
now you should be able to follow the rest
Answer this Question
Pre-Calc - Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= ...
Trigonometry Check - Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [...
Precalculus/Trig - I can't seem to prove these trig identities and would really ...
drwls - My previous question: Verify that (secx/sinx)*(cotx/cscx)=cscx is an ...
Math - Im really struggling with these proving identities problems can somebody ...
Trig - Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(...
Simplifying with Trigonometry Identities - Hi, I am a senior in High School ...
Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...
precal - 1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-...
Pre-Calculus - How do you verify: 1.) sinxcosx+sinx^3secx=tanx 2.) (secx+tanx)/(...